Prescribing in pregnancy for women with diabetes: use of potential teratogenic drugs and contraception. Issue 4 (17th March 2013) - Makda, S. I.; Davies, M. J.; Wilmot, E.; Bankart, J.; Yates, T.; Varghese, E. M.; Fisher, H.; Anwar, A.; Khunti, K.
Abstract Aims To describe contraception use and the prescription of drugs that are either not recommended in pregnancy or are potentially teratogenic by diabetes type in women of child‐bearing age. Methods Retrospective, cross‐sectional chart review undertaken in 22 general practices in Warwickshire, UK. Demographic, anthropometric, medical history, medication and contraception data were extracted from women aged 14 to 49 years with pre‐existing diabetes. Independent sample t‐test, Mann–Whitney test and χ2‐test were used to test for univariable associations and multiple logistic regression was used to adjust for confounders. Results Four hundred and seventy eligible women were identified; the majority had a diagnosis of Type 2 diabetes (67%). Thirty‐six per cent and 64% of women with Type 1 and Type 2 diabetes, respectively, were prescribed drugs not recommended for use in pregnancy (P < 0.001). Less than half were using concomitant contraception (P < 0.001). No significant difference of contraception use was observed between women who were and were not taking drugs not recommended for use in pregnancy (40 vs. 41%, P = 0.4). Conclusions Use of drugs not recommended during pregnancy in women with diabetes of child‐bearing age is common but is not associated with increased use of contraception. There is need to identify and overcome barriers to effective contraception use for this population group in order to facilitate optimal management of cardiovascular risk.